The Role of Pre-therapeutic 18F-FDG PET/CT in Pediatric Hemophagocytic Lymphohistiocytosis With Epstein-Barr Virus Infection - Lu, Xia; Wei, Ang; Yang, Xu; Liu, Jun; Li, Siqi; Kan, Ying; Wang, Wei; Wang, Tianyou; Zhang, Rui; Yang, Jigang (Frontiers in Medicine, 2022)
Objective To evaluate the role of pre-therapeutic 18F-FDG PET/CT in pediatric hemophagocytic lymphohistiocytosis (HLH) with Epstein-Barr virus (EBV) infection. Methods This retrospective study included 29 HLH children (1-16 years) with EBV infection, who underwent pre-therapeutic 18F-FDG PET/CT from July 2018 to November 2020. Pathology results were considered as the reference standard. These patients were divided into two groups: EBV-induced malignancy-associated HLH (M-HLH, N = 9) and EBV-induced non-malignancy-associated HLH (NM-HLH, N = 20). The regions of interest (ROIs) of the liver, spleen (Sp), bone marrow (BM), lymph nodes (LN), hypermetabolic lesions, liver background (LiBG), and mediastinum (M) were drawn with software 3D-Slicer. The volumetric and metabolic parameters, including maximum standard uptake value (SUVmax), metabolic tumor volume, and total lesion glycolysis of these ROIs, clinical parameters, and laboratory parameters were compared between the two groups. The efficiency of the above parameters in predicting the treatment response and overall survival (OS) was analyzed. Results Receiver operating characteristic curve analysis indicated that SUVmax-lesions and SUVmax-LN/M (AUC = 0.822,0.819, cut-off = 6.04, 5.74, respectively) performed better in differentiating M-HLH from NM-HLH. It had the best diagnostic performance when age was added with the SUVmax-LN/M (AUC = 0.933, sensitivity = 100%, specificity = 85.0%). The presence of extranodal hypermetabolic lesions in multiple organs indicated the M-HLH (P = 0.022). Older age, higher SUVmax-LN and SUVmax-lesions, and the presence of serous effusion were associated with poorer treatment response at the 2nd and 4th week (not reaching partial remission). Multivariate analysis showed that SUVmax-lesions > 7.66 and SUVmax-Sp/LiBG > 2.01 were independent prognostic factors for overall survival. Conclusions 18F-FDG PET/CT could be a valuable technique for identifying the underlying malignancy and predicting prognosis in pediatric HLH with EBV infection. M-HLH could be considered when SUVmax-lesions > 6.04, SUVmax-LN/M > 5.74, and the presence of extranodal hypermetabolic lesions in multiple organs on 18F-FDG PET/CT. SUVmax-lesions and SUVmax-Sp/LiBG might be independent prognostic factors for OS.